Harmful drinking is associated with mental health conditions and other risk behaviours in Australian young people. (4th May 2020) - Lima, Fernando; Sims, Scott; O'Donnell, Melissa
Abstract: Objective : To investigate factors associated with alcohol use in adolescents, with the focus on analysing the comorbidities between single‐occasion harmful‐drinking episodes with mental health issues and risk behaviours. Methods : This study used data from the Young Minds Matter survey, designed to inform on the prevalence of the seven most common mental health disorders of children and adolescents. Logistic regression modelling was used to assess the odds of harmful drinking behaviour in young people aged 13–17 years in Australia. Results : We found a strong association between single‐occasion harmful drinking and mental health issues, which hold after controlling for sociodemographic characteristics. Young people with severe mental health issues within the past year were four times more likely to have been drinking at harmful levels in the past 30 days. Conclusions : Alcohol use can have adverse health effects among children and adolescents. Research has found a bidirectional association between alcohol use and mental health conditions where the presence of one issue almost doubles the risk of having the other issue. Implications for public health : The comorbidity between these issues suggests the need for strategies to integrate policies addressing mental health and alcohol use disorders in young people.